(3QSGdI aJM GdYdje GdHGSW aj QSe GdCQHGY hGdHSGFWs - (3eMeO CHi YjGTI GdTGaYj GdOefghQis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3gPg QSGdg ai QSe GdCQHGY hGdHSGFW QJHJgG Ydi ebOeI hEKfG YTQ HGHkG hNGJeI s
(3BNQgG (B:s
(3JWQMgG ef LjH JeGe GdYQV jMUd aVd GdLjHjf hJeGe GdYed s
(3CdaJ SfI (B1273 (3ajgG HYV GdQShe GdgfOSjI hHYV GeGcf GdQShe NdJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B726 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B52 s
Keywords: (3Gdadcs